Extended view on the dust shells around two carbon stars - Mečina, Marko; Aringer, B.; Nowotny, W.; Groenewegen, M. a. T.; Kerschbaum, F.; Brunner, M.; Gail, Hans-Peter (Astronomy and astrophysics, 2020)
Context. Stars on the asymptotic giant branch lose considerable amounts of matter through their dust-driven stellar winds. A number of such sources have been imaged by Herschel/PACS, revealing a diverse sample of different morphological types. Among them are a few examples which show geometrically thin, spherically symmetric shells which can be used to probe the mass loss history of their host stars.Aims. We aim to determine the physical properties of the dust envelope around the two carbon stars U Hya and W Ori. With the much-improved spatial constraints from the new far-infrared maps, our primary goal is to measure the dust masses contained in the shells and see how they fit the proposed scenarios of shell formation. Methods. We calculated the radiative transfer of the circumstellar dust envelope using the 1D code More of DUSTY (MoD). Adopting a parametrised density profile, we obtained a best-fit model in terms of the photometric and spectroscopic data, as well as a radial intensity profile based on Herschel/PACS data. For the case of U Hya, we also computed a grid of circumstellar envelopes by means of a stationary wind code and compare the results of the two modelling approaches.>Results. The Herschel/PACS maps show U Hya surrounded by a detached shell of 114′′ (0.12 pc) in radius, confirming the observations from previous space missions. The dust masses calculated for the shell by the two approaches are consistent with respect to the adopted dust grain properties. In addition, around W Ori, we detect for the first time a weak spherically symmetric structure with a radius of 92′′ (0.17 pc) and a dust mass of (3.5 ± 0.3) × 10−6M⊙.